Wildlife Research and Monitoring in Nepal: An Overview - Poudel, Buddi Sagar (The Initiation, 2010)
Considerable research studies have been carried out in protected areas of Nepal over last three decades. Often, these studies are species oriented on selected endangered mammals and do not deliver conservation actions potentially to serve management needs. Comprehensive, multidisciplinary research approach and long term monitoring is scant at present and is of little conservation significance. Research policies, guidelines, prioritization and evaluation criteria are important facets for sound protected area management. Persistent concerted efforts are needed to make research and monitoring as an integral part of protected area management. This paper reviews present state of wildlife research in Nepal's protected areas. The conservation laws and regulation related to research studies are dealt in brief. Also, the endangered species monitoring exercises are discussed and finally, this paper offers some prospective options to make the protected areas as learning centers from conservation standpoint and recommends documentation and dissemination of researched information. Key Words: Protected area, Research & monitoring, Rhino, Tiger, Gharial, Gaur, Swamp deer. DOI: 10.3126/init.v2i1.2515 The Initiation Vol.2(1) pp22-32